Usage of Blockchain Technology in Real Estate Transactions in Lagos State, Nigeria - Adebisi, Oluwasola; Afolabi, Omolola; Olaniyi, Olusola Kehinde (Journal of African Real Estate Research, 2025)
The study examined the use of blockchain technology in real estate transactions in Lagos State, Nigeria, by assessing the level of adoption among estate surveying and valuation firms and the factors influencing its adoption. The data for this study were collected through questionnaires administered to estate surveying and valuation firms located on Lagos Island, Lagos State. The questionnaires provided the firms’ opinions on the adoption of blockchain technology, their level of awareness of blockchain technology and the factors influencing its adoption. The data analysis revealed that real estate practitioners were very aware of various blockchain applications, including fintech, cryptocurrency, smart contracts, and cross-border transactions, which are useful tools that estate surveyors and valuers can adopt in real estate practice and transactions. Furthermore, the analysis revealed that regulatory challenges, trust issues, and poor internet provision compromise the adoption and usage of blockchain technology in Lagos State. The study recommends frequent sensitisation of members by the Nigerian Institution of Estate Surveyors and Valuers and the creation of an enabling environment by the government, as the use of this emerging technology is facilitated by infrastructure such as regular internet and electricity supply.